The Effect of Transformational Leadership on Organizational Performance Through the Mediating Role of Organizational Culture in Higher Education Institutions in Iraq - Mohammed Ahmed Waham,; Rahman , Rafiduraida Abdul; Mustaffa, Wan Salmuni Wan (International Journal of Psychosocial Rehabilitation, 2020)
Today, most of educational institutions in higher education sector need for leaders who are willing to works with subordinates to identify needed change, creating a vision to guide the change through inspiration, and executing the change in tandem with committed members of a group. Higher Education in Iraq faces many challenges which affected the educational performance of most universities in Iraq. Thus, the aim of this study is to investigate the effect of transformational leadership on organizational performance of Iraqi universities as well as examining the mediating effect of organizational culture on the relationship between transformational leadership and organizational performance. The problem that is discussed in this study is the inability of leaders in higher education institutions to face the challenge of being effective to boost the performance of their universities which is reflected on the ability of Iraqi universities to compete in higher education market. The result of this study showed that transformational leadership in educational institutions affected the performance of universities and mediated by the culture of the organizations. The methodology used in this study is based on a quantitative methods and survey. Population and sample consist of individuals represent academics staff in five universities located the south area of Iraq. The significance of this study comes from the analysis of essential factors that enhance the performance of educational institutions in Iraq.